Is rivaroxaban a cost‐effective anticoagulation therapy compared with warfarin?. Issue 10 (October 2017) - Hawks, Matthew; Moss, David
Abstract : Bottom line : Yes. For the treatment of atrial fibrillation, patients given rivaroxaban have similar or lower total costs than patients given warfarin (including medications, laboratory costs, hospitalizations, outpatient/emergency visits, and transportation) over the short term (SOR: B, consistent cohort studies). Rivaroxaban is also likely cost effective after 16 years compared with warfarin for treatment of nonvalvular atrial fibrillation (NVAF) (SOR: B, cost‐effectiveness simulation). For treatment of venous thromboembolism (VTE), there is a 98% likelihood that rivaroxaban is cost saving compared with warfarin (SOR: B, cost‐effectiveness simulation).